Using Visualization to Support Network and Application Management in a Data Center - Warncke, Heather; Maltz, David A.; Wang, Xiaoyu; Greenberg, Albert; Fisher, Danyel; Czerwinski, Mary; Robertson, George; Maltz, Dave (Internet Network Management Workshop at ICNP, 2008)
We argue that there is a continuum between completely manual and completely automated management of networks and distributed applications. The ability to visualize the status of the network and applications inside a data center allows human users to rapidly assess the health of the system – quickly identifying problems that span across components and solving problems that challenge fully autonomic and machine-learning based management systems. We present a case study that highlights the requirements on visualization systems designed for the management of networks and applications inside large data centers. We explain the design of the Visual-I system that meets these requirements and the experience of an operations team usnig Visual-I